Lower serum insulin-like growth factor-1 levels are independently associated with anemia in patients undergoing maintenance hemodialysis - Shilin Xu; Jun Ren; Yuping Yao; Danping Qin; Yan Liu; Xiaoshi Zhong; Rongshao Tan; Chunjie Jiang; Yun Liu; Wenxuan Chen (Renal Failure)
The relationship between serum insulin-like growth factor-1 (IGF-1) levels and anemia in patients undergoing maintenance hemodialysis (MHD) remains unclear. This cross-sectional study included patients who underwent MHD treatment for >3 months at our dialysis center in March 2021. Demographic and clinical data were recorded. Blood samples were collected before the hemodialysis sessions, and general serum biochemical parameters, routine blood markers, and serum IGF-1 levels were measured. Patients were divided into a group without anemia (hemoglobin ≥110 g/L) and a group with anemia (hemoglobin <110 g/L), and multivariable linear and binary logistic regression analyses were performed to study the relationship between the levels of serum IGF-1 and anemia. A total of 165 patients (male/female = 99:66) with MHD were enrolled in the study, with a median age of 66.0 (58.0, 75.0) years and a median dialysis vintage of 27.0 (12.0, 55.0) months. The mean hemoglobin level was 96.38 ± 16.72 g/L, and 126 patients had anemia (76.4%). Compared to patients without anemia, patients with anemia had lower serum IGF-1 and triglyceride levels and higher intravenous iron supplementation on dialysis (all p < 0.05). After adjusting for confounding factors in different models, the nine-model multivariate binary logistic regression analyses also confirmed that lower serum IGF-1 levels and serum IGF-1 < 197.03 ng/ml were both independently associated with anemia in patients undergoing MHD. However, further multicenter studies with larger sample sizes are required to confirm these findings.